Propuesta de un manual de funciones por competencias, valuación de puestos por puntos y reglamento de admisión para la empresa florícola el campanario de Santa Anita S.C.C. de la ciudad de Latacunga - Martínez Lalangui, Ximena Janeth (2016)
The following study was elaborated at Rose Plantation El Campanario de Santa Anita S.C.C. Located in Cotopaxi province. The main objective in this study is to propose a Competency-based functions manual, job valuation scores, and admission policy based on the Company´s needs of having a tool that allows it to recruit the personnel suitable for each job, valuating each person knowledge, abilities and skills, thus increasing the company´s activities efficiency. The primary objective of this manual is to indicate clearly functions all activities of the company and distribute responsibilities in each of the counts of the same . The manual functions is an information tool which is described chronologically sequential operations to be followed to perform the functions in a company. The valuation placed on points, is a technical procedure used to determine the relative value of a position in front of others and to set the salary of a class of position. Job evaluation points is the most common of all the existing method as it allows the assessor to apply a broader view, because it analyzes the position in each of the factors and sub factors that shape it , unlike those who appreciate the position as a whole. For admission staff the company has recommended implementing or regulation of admission and employment same begins with recruitment where established policies relating to recruitment sources ; selection continues the section in which the stages that make up this phase is specified ; then hiring that takes place once the right person for the position chosen , contains the registration of the contract , induction , training the new employee to his job and performance evaluation test period ; this process will allow the integration of appropriate personnel to the company helping to improve productivity. To meet the objective methods as were used: Inductively through which theoretical information that supports the development work was collected . Deductive method in the interpretation of the results of the surveys and interviews conducted . Analytical method for diagnosis of the current situation . Synthetic was used to summarize the information and detect the most relevant information for the construction of competency manual functions , the valuation of positions points and the rules of admission and employment . Statistical method was used for the application of different formulas and calculations. The survey was applied to 99 employees : The following techniques were used . The interview with the Head of Human Resources and Direct observation allowed to know the functional organizational structure of the company. After analyzing the data from the survey applied to 99 employees , the following results are obtained: it was determined that most of the staff belongs to the operational area , while a smaller percentage is the administrative area . Of all staff surveyed , 55% say they have basic education , 38% state that have baccalaureate , 1% are technicians , 4% disclosed that they have title of third level while 2 % have title fourth level. Similarly , 93 % said they made them interview for entry to work , 56% disagree with the salary received according to their activities and functions , 75 % say they have not been informed in writing activities that have to make 100% express unfamiliar existing in the company manual functions . Finally the conclusions of all the research work where details each of the results obtained from the various sources of collected information was made , therefore it is recommended to accept the proposal put forward which has been designed in such a way as to facilitate the flow of information , allowing the use of human talent .